MUSIK SEBAGAI TEMAN BELAJAR : STUDI ETNOGRAFI PENDIDIKAN DI SD MUHAMMADIYAH TERPADU PONOROGO - ALMINIATI , ALMINIATI (2011)
The objectives of this research are: (1) To describe the characteristics of the various learns of music which are accompanying the teaching learning process at SD Muhammadiyah Terpadu in Ponorogo; (2) To describe the characteristics of the teaching learning process accompanied by listening to the musik at SD Muhammadiyah Terpadu in Ponorogo; (3) To describe the characteristics of the students behavior during the teaching learning process accompanied by music at SD Muhammadiyah Terpadu in Ponorogo. This research design used in this study is descriptive qualitative.The instruments to collect data are observation, questionnaire and documentary. The source of data is taken from the school community causiting of directur, teachers, students, and student parents. The setting of place is SD Muhammadiyah Terpadu located in Jl. Jagadan no. 14 Ponorogo East Java. Data has been collected is analysed by using domain analysis, taxonomy analysis, componensial analysis, and cultural theme based analysis. The findings of the research are the following: (1) The characteristics of musics accompanying students learning are in the form of Islamic musicsfor any activites from their caming to learning. The musics are softly played. For various interest like welcome music, music for signing tunch time, prayer time, free time, extracurriruler time, exorcise, and lesson shift, and parting time. The types of instrumentalia used in SDMT are adapted from Mozart, Bettoven, Sympony, Sonata, Canon, Adagio in G. Minor, and qosidah musics; (2) The learning process was warked well with musics. The learning was done by active learning, peer learning, and joyful learning (PAKEM) approaches; (3) Student behaviors accompanied by musics motivated, antusiastic, dynamis, relax, and condusive. Their motivation to attend to the school is getting better and their absentism was low but qickness and family needs. They looked happy, creative, dynamic, relax, within the classroom except the inclusive students (ABK).